Organização domiciliar e escravidão no extremo sul do Brasil: Caçapava no século XIX - Corrêa, André do Nascimento (Universidade do Vale do Rio dos Sinos, 2017)
This work aims at analyzing some social configurations of the locality of Caçapava, a region located in the south of Brazil. In this sense, the focus of this analysis is on the domiciles and issues that pervade slavery in Caçapava. For this purpose, we can rely on some fundamental documents for this research, such as: a list of fires of the year 1830 and all inventories between 1821 and 1850. To include other aspects of this social analysis, we added the inventories of the registry of Orphans and Absentees, cataloged by the APERS, between 1851 and 1871, as well as all the letters of freedom of registry between 1835 and 1871. In this way, the research extends from 1821 to 1871. In this sense, we seek to characterize the inhabitants of the locality, as well as the process between the slavery and freedom that were inserted in this context, showing the ways in which the enslaved had to achieve their freedom. We did an economic analysis, to understand how the social agents present in the analyzed documents were inserted in this process, to enable us to visualize the size of the units of production and characterize them according to their size. Thus, the data presented in some of the cited documents, allow us to understand how this locality was organized. We have, therefore, applied as methodology the principles of serial, quantitative and qualitative history.
Keywords: Escravidão; Hierarquia social; Organização domiciliar; Pecuária; Slavery; Social hierarchy; Home organization; Livestock; ACCNPQ::Ciências Humanas::História